Social networks and informal financial inclusion in the people's republic of China - Shijun Chai; Yang Chen; Bihong Huang; Dezhu Ye (Asian Development Bank Institute (ADBI), 2018)
Using the 2011 China Household Finance Survey (CHFS) database, we explore the heterogeneous impacts of social networks on informal financial inclusion for urban and rural households in the PRC. We find that social networks significantly increase the probability of households' participation in the informal financial market, augment the size of informal financial transactions, and raise the ratio of informal lending to total household assets. We also identify the mechanisms through which social networks affect households' participation in the informal financial market. By reducing the information cost, perceived risk, and precautionary saving, social networks play a larger role for urban households than for rural households. Notably, the effects of social networks on informal finance are strengthened by the development of the formal financial market.
Keywords: D1; G2; 330; social networks; informal financial inclusion; perceived risk; precautionary saving; formal financial market